CD81 and CD48 show different expression on blood eosinophils in systemic sclerosis: new markers for disease and pulmonary inflammation?. (3rd March 2016) - Wuttge, DM; Andreasson, A; Tufvesson, E; Johansson, ÅCM; Scheja, A; Hellmark, T; Hesselstrand, R; Truedsson, L
Abstract : Objectives: In systemic sclerosis (SSc)-related interstitial lung disease (ILD), elevated eosinophil counts in bronchoalveolar lavage are associated with a worse outcome. We hypothesized that eosinophils may be activated in the peripheral circulation, thereby increasing their recruitment to affected tissues and contributing to inflammation and fibrosis. The aim of this study was to characterize the blood eosinophils in SSc patients. Method: Expression levels of surface markers CD11b, CD44, CD48, CD54, CD69, CD81, and HLA-DR on CD16 low CD9 high -expressing eosinophils were measured by flow cytometry in whole blood from SSc patients (n = 32) and controls (n = 11). Results: Expression levels of CD54, CD69, and HLA-DR were undetectable in all groups. CD44 and CD11b expression levels were similar between groups. CD81 expression was lower in patients compared to controls independent of disease duration (p = 0.001). CD48 expression was increased in patients with a short disease duration (< 2 years) compared to both controls (p = 0.042) and patients with longer disease duration (≥ 2 years; p = 0.027). In patients with short disease duration, increased CD48 expression was associated with alveolar inflammation as measured by an increased concentration of alveolar nitric oxide (r = 0.76, p = 0.003). Conclusions: Blood eosinophils change phenotype during disease evolution in SSc, and CD48 expression may be used as a biomarker for pulmonary inflammation.